2019
DOI: 10.1186/s43044-019-0027-x
|View full text |Cite
|
Sign up to set email alerts
|

Endomyocardial fibrosis presented by ventricular tachycardia: case report

Abstract: BackgroundEndomyocardial fibrosis (EMF) is a form of restrictive cardiomyopathy that is diagnosed mainly in children and young adults and is geographically found in Africa, Latin America, and Asia. It is a condition with high morbidity and mortality, unknown etiology, and no definitive treatment. Although its main clinical presentation is congestive heart failure with or without related supraventricular arrhythmia like atrial fibrillation, it very rarely presents with ventricular arrhythmias and tachycardias (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Different from previous studies, which showed that heart failure and supraventricular tachycardia are common and ventricular arrhythmia are rare [30], the present cohort found a prevalence of 10.2% (N = 117) of VT. The mechanism of VT in patients with RCM is still unclear, and may be related to myocardial amyloid deposition [31] or subendocardial infarction and fibrosis [32]. Of note, VT is associated with increased mortality [33][34][35][36] but heart failure induced by VT doubles the patient's risk of death with each NYHA grade increase [16].…”
Section: Discussionmentioning
confidence: 99%
“…Different from previous studies, which showed that heart failure and supraventricular tachycardia are common and ventricular arrhythmia are rare [30], the present cohort found a prevalence of 10.2% (N = 117) of VT. The mechanism of VT in patients with RCM is still unclear, and may be related to myocardial amyloid deposition [31] or subendocardial infarction and fibrosis [32]. Of note, VT is associated with increased mortality [33][34][35][36] but heart failure induced by VT doubles the patient's risk of death with each NYHA grade increase [16].…”
Section: Discussionmentioning
confidence: 99%
“…The initial phase of the disease is acute carditis, characterized by febrile illness, and in some cases, it progresses to cardiogenic shock. But the vast majority present during the chronic phase with symptoms of heart failure, arrhythmia, and thromboembolism 1,4 …”
Section: Discussionmentioning
confidence: 99%
“…But the vast majority present during the chronic phase with symptoms of heart failure, arrhythmia, and thromboembolism. 1,4 Generally, the main pathological event is unknown. However, there are multiple theories about its development, and further studies are needed to unfold its etiologies further and help us understand it better.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial phase of the disease is acute carditis, characterized by febrile illness and in some cases, it progresses to cardiogenic shock. But the vast majority present during the chronic phase with symptoms of heart failure, arrhythmia and/or thromboembolism (1,4).…”
Section: Case Presentationmentioning
confidence: 99%